Clinical and Laboratory Characteristics of Symptomatic and Asymptomatic Neurosyphilis in HIV-Negative Patients: A Retrospective Study of 264 Cases. (6th May 2019) - Li, Wurong; Jiang, Meijuan; Xu, Dongmei; Kou, Cheng; Zhang, Lei; Gao, Junhua; Qin, Kaiyu; Wu, Wenqing; Zhang, Xinghu
Abstract : A retrospective study was performed to compare the differences in clinical and laboratory features of asymptomatic neurosyphilis (ANS) and symptomatic neurosyphilis (SNS). A total of 264 HIV-negative inpatients with neurosyphilis were enrolled from Beijing Ditan Hospital and Beijing Tiantan Hospital between January 2014 and May 2018, including 110 SNS and 154 ANS. The SNS group had more patients in males, older median age and without antisyphilis treatment than ANS group (P<0.001, P<0.001, and P<0.001, respectively). The laboratory findings showed that the SNS group had higher pretreatment serum rapid plasma regain (RPR) titer, current serum RPR titer, cerebrospinal fluid (CSF) white blood cell (WBC) counts, CSF protein concentrations, and higher positive CSF RPR rate than those in the ANS group (P=0.011, P<0.001, P<0.001, P<0.001, and P<0.001, respectively). The multivariate logistic regression analysis revealed that male (OR=2.833, P=0.009), age≥45 years (OR=3.611, P=0.001), without antisyphilis treatment (OR=0.247, P<0.001), higher current serum RPR titer (OR=1.373, P=0.022), positive CSF RPR (OR=4.616, P<0.001), and higher CSF protein concentration (OR=1.017, P=0.026) were independent risk predictors for SNS. Therefore, clinical and laboratory features between SNS and ANS are quietly different. Male gender, age≥45 years, and lack of antisyphilis treatment are risk factors for SNS. The elevated level of serum RPR titer, CSF protein concentration, and CSF RPR titer may indicate the development of neurosyphilis and the aggravation of neurological symptoms.